Growing international evidence for urinary biomarker panels identifying lupus nephritis in children – verification within the South African Paediatric Lupus Cohort. (December 2018) - Smith, E M D; Lewandowski, L B; Jorgensen, A L; Phuti, A; Nourse, P; Scott, C; Beresford, M W
Background: A urinary biomarker panel including alpha-1-acid-glycoprotein (AGP), lipocalin-like-prostaglandin-D-synthase (LPGDS), transferrin and ceruloplasmin demonstrates an 'excellent' ability for identifying active lupus nephritis in UK/US children. This study aimed to assess whether this panel identifies active lupus nephritis within the South African Paediatric Lupus Cohort. Methods: Juvenile-onset-systemic lupus erythematosus( JSLE) patients aged < 19 years at diagnosis and healthy controls were recruited. Patients were categorized as having active lupus nephritis (renal BILAG score; A/B and previous histological confirmation) or inactive lupus nephritis (renal BILAG score: D/E). Urinary biomarkers were quantified by ELISA. Mann–Whitney U -test compared biomarker levels between groups. Binary logistic regression and receiver operating curve analysis assessed biomarker combinations. Results: Twenty-three juvenile-onset-systemic lupus erythematosus patients were recruited with a median age of 13.5 years (interquartile range (IQR) 12.7–14.9) and disease duration of 2.6 years (IQR 1.8–4.0). Eighteen healthy controls had a median age of 11.0 years (IQR 10.0–12.0). AGP, LPGDS, transferrin, ceruloplasmin and VCAM-1 were significantly higher in active than in inactive lupus nephritis patients (corrected p -values, all p c  < 0.05), with no difference between inactive lupus nephritis patients and healthy controls (all p c  = 1.0). The optimal biomarker combination included AGP, ceruloplasmin, LPGDS and transferrin (area under the curve = 1.0). Conclusions: A urinary biomarker panel comprising AGP, ceruloplasmin, LPGDS and transferrin previously validated within UK/US cohorts also performed excellently within a racially distinct South African cohort which displayed more severe lupus nephritis.